PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING PADA MATA PELAJARAN MATEMATIKA MATERI PENJUMLAHAN BERSUSUN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS 1 SDI ASH-SHIDDIQ BUDURAN SIDOARJO - Kartikasari, Hikmah Luqiyah; Tsalitsah, Nurus; Nuro, Lailin; Darojat, Zakiyah (Jurnal Muassis Pendidikan Dasar, 2024)
From the observations, it was found that problems in the learning process that grade 1 students of SDI Ash-Shiddiq Buduran Sidoarjo had difficulty in receiving subject matter, especially in mathematics subjects, stacked addition material so that it affected student learning outcomes. With these problems, researchers try to apply creative problem solving  learning models. With the hope, this research can improve the activities and learning outcomes of students.  The research method used in this study is class action research which is carried out in two cycles. The results showed that applying  the creative problem solving  learning model can improve student learning outcomes. This is evidenced by observation data on teacher and student activities and student learning outcomes. Teacher activity in the first cycle obtained a percentage of 70.5%, which means that it has not reached the specified success indicator of ≥76%. In cycle II it has obtained a percentage of 100%. While the activity of students in cycle I obtained a percentage of 50% while in cycle II has achieved success indicators, namely obtaining 100%. The learning outcomes of students in the first cycle obtained 67%, which means that they have not reached the set learning outcomes completeness indicator of ≥80%. While in cycle II the learning outcomes of students have increased, obtaining a percentage of 92%. Thus, it can be concluded that the application of the creative problem solving  learning model can improve student learning outcomes in mathematics learning of grade 1 stacked addition material SDI Ash-Shiddiq Buduran, Sidoarjo.